The community based tourism-experience in Yunguilla, Ecuador and its social-cultural impact in the community - Neudel, York (2015)
At first sight, community-based tourism seems to be an alternative to mass tourism with less environmental and social-cultural impact for the host community. It has the reputation of providing authentic and real experiences for tourists, while generating income and jobs for the local population. In 1996 a community based tourism project was launched in Yunguilla, a village located in the north of the Metropolitan District of Quito, Ecuador. This article analyzes the social-cultural impacts this program has had on that community nearly two decades later. Through In-depth interviews with hosts and guests, fieldwork during one and a half year and the examination of archives, this work brings to light the thin line between risks and advantages for a society that inserts itself to a capitalist mechanism with its principles of supply and demand.